The use of state-of-the-art transport models by policymakers – beauty in simplicity?. (2nd July 2016) - Givoni, Moshe; Beyazit, Eda; Shiftan, Yoram
Abstract: Transport demand models have a long history of being a major tool in transport policy making. However, whether they are truly used in decision-making processes, and if so, whether the knowledge they provide is actually understood, is questionable. The potential contribution they can make and the importance of such models is not disputed; however, evidence shows that many issues arise with their actual use that severely limits their potential contribution. Based on case study methodology and analysis of the use of models in the transport policy processes in two countries, the UK and Israel, this paper aims to provide empirical evidence of the issues contributing to limiting the potential contribution of models and to make recommendations for better utilisation of the knowledge they can produce. The main conclusion reached is that transport models must be made simpler if they are to contribute more than they currently do to decision-making in transport policy and planning.